Degradation mechanism of dielectric loss in barium niobate under a reducing atmosphere - Kim, Dong-Wan; Kim, Byung-Kook; Je, Hae-June; Park, Jae-Gwan; Kim, Jeong-Ryeol; Hong, Kug Sun (WILEY, 2006)
We developed multilayer ceramic capacitors (MLCCs) of the type negative-positive zero (NP0) cofired with Cu inner electrodes using novel low-loss barium niobates. The excellent dielectric properties of ceramics and compatibility between electrodes and dielectrics under a reducing atmosphere led to low loss character in the Cu-MLCCs, even in the high-frequency single-layer capacitors. We also examine the atmospheric dependence on dielectric loss of barium niobates. The origin of degradation in dielectric loss under a highly reducing atmosphere is explained by the association of two loss mechanisms: the oxygen vacancies in NbO6 octahedra and the subsequent formation of a reduced second phase: Ba3Nb4+Nb45+O15.
Keywords: MULTILAYER CERAMIC CAPACITORS; TEMPERATURE; BA5NB4O15; TITANATE